METHODS OF CONCENTRATION OF AUDIENCE ATTENTION IN THE PROCESS OF STUDYING THE DISCIPLINE "METROLOGY STANDARDIZATION AND INTERCHANGEABILITY" (Academia Science Repository, 2023)
The authors of the article suggest that teachers, in order to concentrate the attention of students, when conducting classroom classes, rely on their biological and psychological characteristics. The authors of the article consider methods of influencing students for an effective learning process, such as: musical, linguistic, visual, kinesthetic, personal, interpersonal. It is concluded that all of the above methods work well and can be used by teachers for work.